2009
DOI: 10.1074/jbc.m109.043364
|View full text |Cite
|
Sign up to set email alerts
|

Calnexin Improves the Folding Efficiency of Mutant Rhodopsin in the Presence of Pharmacological Chaperone 11-cis-Retinal

Abstract: The lectin chaperone calnexin (Cnx) is important for quality control of glycoproteins, and the chances of correct folding of a protein increase the longer the protein interacts with Cnx. Mutations in glycoproteins increase their association with Cnx, and these mutant proteins are retained in the endoplasmic reticulum. However, until now, the increased interaction with Cnx was not known to increase the folding of mutant glycoproteins. Because many human diseases result from glycoprotein misfolding, a Cnx-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
(46 reference statements)
0
37
0
Order By: Relevance
“…In these disorders, the mutant protein undergoes misfolding and forms toxic aggregates in the cytosol (58,59). We provide evidence for the aberrant accumulation of a protein in photoreceptors that seems to function downstream of the mutated disease protein Cep290.…”
Section: Discussionmentioning
confidence: 92%
“…In these disorders, the mutant protein undergoes misfolding and forms toxic aggregates in the cytosol (58,59). We provide evidence for the aberrant accumulation of a protein in photoreceptors that seems to function downstream of the mutated disease protein Cep290.…”
Section: Discussionmentioning
confidence: 92%
“…We found that an increase in rhodopsin expression was damaging to wild-type photoreceptors, but was protective to photoreceptors bearing the P23H transgene on the same background. However, the level of rhodopsin protein in the P23H transgenic mice is much lower than that in C57Bl/6 mice (Noorwez et al, 2009). As even wild-type opsin can misfold and aggregate, it is not surprising that a little extra is too much.…”
Section: Discussionmentioning
confidence: 99%
“…To determine if overexpression of rhodopsin from viral delivery damaged the retinas of wild-type mice, we injected AAV-RHO301 in C57BL/6J mice, which accumulate more rhodopsin than the P23H transgenic mice (Noorwez et al, 2009). Proteins were also extracted from wild-type C57BL/6J mice retinas 1 month after subretinal injection, and expression of rhodopsin was detected by anti-rhodopsin monoclonal antibody 1D4.…”
Section: Aav-rho301 Delivery Damages Wild-type Retinasmentioning
confidence: 99%
“…6C), as well as a global increase of the ∼28-, ∼36- and ∼45–60-kDa species of Rho(P23H), which correspond to an N-terminal truncated protein, the EndoH-sensitive glycoform and dimer, respectively (Fig. 6D) (17,29,47). These findings suggest that silencing of ERdj5 can affect the traffic of WT rod opsin and can increase accumulation of P23H in the ER, thus making it more prone to aggregation.…”
Section: Resultsmentioning
confidence: 98%